KEBIJAKAN PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM (Studi Histori dan Regulasi di Indonesia) - Mufarrihul Hazin; Nur Wedia Devi Rahmawati (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2021)
The curriculum becomes an important component in education. Therefore, the development of curriculum in Islamic education is an inevitability, because change must happen with the times. Therefore, the purpose of this writing will be to review the policy of developing of islamic education curriculum, especially in Indonesia by taking into history and regulations. This article uses library research method with content analysis approach.  The results showed that the Curriculum Development of Islamic Education in the historical review from the independence period to the reform era continues to change according to the conditions and needs. The development of Islamic education curriculum is divided into 3 periods; i.e.  first,  the old order period, there were 3 changes, namely the curriculum in 1947, 1952, and the curriculum in 1964; second, the new order period, there were 4 changes, the curriculum 1968, 1975, 1984, and curriculum 1994; third, the reform period, there have been 3 changes, the 2004 curriculum (KBK), curriculum 2006 (KTSP), curriculum 2013 used until now. While in the review of islamic education curriculum regulation there are 4 categories,  first,  the regulation of madrasah curriculum follows Law Number 20 of 2003 about national education system; second,  the regulation of pesantren curriculum follows Law Number 18 of 2019 about Pesantren; third,  the regulation of islamic religious college curriculum induces Law Number 12 of 2012 about higher education; and  fourth, the regulation of Islamic religious education curriculum for schools / public campuses induces Law Number 20 of 2003 about natioal education system.